RESPON PERTUMBUHAN TANAMAN KAYU KUKU (Pericopsis mooniana) DENGAN MENGGUNAKAN PUPUK NPK - Andini Dyah Hernanda; Eny Dwi Pujawati; Adistina Fitriani (Jurnal Sylva Scienteae, 2022)
The purpose of this study was to determine the percentage of nail wood seedlings and to determine the effect of the concentration of NPK fertilizer on the growth of nail wood seedlings. Parameters used include plant height, plant diameter, plant health. Based on the results of the study, the percentage of survival for nail wood grew medium success, namely 70% with 28 live seedlings from 40 seedlings, the highest percentage of survival was found in the NPK fertilizer dose of 7gr (80%) and the smallest was found in the control (60%). The increase in nail wood height with the highest value was in the treatment (2.5gr) with an average value of 3.9cm and the lowest value was found in the control. The diameter of the nail wood has the highest value at 5gr with an average value of 0.9cm increase. The increase in the number of leaves was not significantly different between the controls, 2.5gr, 5gr, and 7.5gr because the average leaf growth was 3 strandsAdapun maksud percobaan ini ialah demi memahami keuntungan semai kayu kuku serta mengetahui kontrol konsentrasi Pupuk NPK terhadap pertumbuhan semai kayu kuku. Parameter yang  digunakan diantaranya, tinggi tanaman, diameter tanaman, kesehatan tanaman. Berdasarkan hasil penelitian Persentase hidup kayu kuku tumbuh keberhasilan sedang yaitu 70% dengan 28 bibit yang hidup dari 40 bibit, persentase hidup tertinggi terdapat pada dosis pupuk NPK 7gr (80%) dan yang terkecil terdapat pada Kontrol (60%). Pertambahan tinggi kayu kuku dengan nilai tertinggi yaitu pada perlakuan (2,5gr) dengan nilai rata-rata 3.9cm dan nilai terendah terdapat pada kontrol. Diameter kayu kuku nilai tertinggi pada 5gr dengan nilai rata-rata pertambahan 0.9cm. Pertambahan jumlah daun tidak berbeda nyata antara kontrol, 2,5gr, 5gr, 7,5gr karena pertumbuhan daunnya rata-rata 3 helai.